Investigation of nicknames in a bilingual environment - Bauko, Ján (Wydawnictwo „Poznańskie Studia Polonistyczne" i Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2012)
The author examines the use of nicknames by the Hungarians in Slovakia. Since the state and the verbal representation of nicknames are strongly influenced by the Hungarian-Slovak bilingual environment, the appearing contact phenomena in the anthroponymic corpus are also investigated in this study. In addition, the paper deals with written nicknames found in written sources, the denomination motives of nicknames used in modern language, sociolinguistic, dialectological, etymological, morphological, and stylistic peculiarities found in the onomastic corpus. The usage of nicknames of adults and students is confronted and discussed with reference to an empirical and comparative study.
Keywords: onomastics; bilingual environment; nicknames; anthroponyms; use of nicknames by Hungarians in Slovakia; anthroponyms, nicknames,